(untitled) (Prosiding Keislaman dan Sains, 2025)
This research aims to find out the legal relationship between contracts, agreements, and engagements in the practice of debt and credit from the perspective of civil law and Islamic law. The type of research used in this research is library research. This research is also a normative legal research with a qualitative approach. The data sources used in library research consist of primary data sources and secondary data sources. The primary data sources in this research are the Civil Code and Islamic law. Secondary data sources in this research consist of textbooks, journals, scientific articles, and other literature related to contracts, agreements, bonds, and debts. The result of this research is that the agreement serves as the foundation for the contract, which then provides a binding legal form. Furthermore, the law of engagement in civil law creates obligations for debtors. Meanwhile, debts are a special type of obligation that includes the obligation to make payments. All these elements are interconnected and form the legal framework underlying the practice of debt and credit. Islam strongly upholds the harmony between contracts, agreements, bonds and fulfilling debts that become agreements, so this is a form of honesty in sharia principles.